Review paperKoebner phenomenon. History and modern aspects of its pathogenesis - Baran, Wojciech; Batycka, Aleksandra; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Koebner phenomenon was first described over 130 years ago and is still an important clue in the differential diagnosis of the skin diseases. Every year, the list of dermatoses in which Koebner phenomenon was described and the provoking factors is longer. The main researches performed to explain the mechanism of the development of this phenomenon concern patients with psoriasis and few hypotheses are the matter for debate. Until now the exact pathomechanism is still unknown and because of the multiplicity of causal factors the multifactorial etiology of this phenomenon is the most probable. In this article modern aspects of pathogenesis of Koebner phenomenon and some biographic facts about Heinrich Koebner are presented.